Why Brazil did not develop a merchant marine; Brazilian shipping and the world in the 19th century - Holten, Birgitte (História Econômica & História de Empresas, 2012)
The weak performance of the Brazilian merchant marine is surprising, as a huge external sector is normally expected to gohand in hand with the development of anational merchant marine. To elucidate this question, the article proposes an analysis and discussion of the development of the Brazilian merchant marine in the nineteenth century. The early focus on the extremely specialized importation of African slaves led to a near abandon of long distance shipping when this trade was banned in 1830. The same tendency to desist from exterior shipping can also be found in the United States in the late 19th century. A comparison of the two countries demonstrates, that the need for developing the national territory and for providing transportation facilities for the growing interior economies diverted the concentration from exterior ventures tonational ones.